Impact assessment of CFLD on Chickpea for productivity, adoption and profitability in Sawai Madhopur District of Rajasthan - Nupur Sharma,; B.L. Dhaka,; B.L. Meena, (Annals of Agricultural Research, 2024)
Step into the heart of agricultural ingenuity as we unveil a pioneering cluster frontline demonstration at farmer’s field, where innovation and sustainable practices unite to cultivate a brighter tomorrow. The present study was carried out to evaluate the impact of pulse production under Cluster frontline demonstration conducted under National Food Security Mission in adopted villages since 2018-19 to 2022-23 in terms of Yield and economics, Adoption and horizontal spread of ICM technologies. Demonstrations were conducted in 110 ha area with 250 farmers in 5 Blocks of Sawaimadhopur during these years. Results revealed that the Average yield of Integrated Crop Management plots were increased gradually over the year from (2093 – 2171q ha-1) which was significantly higher over FP from (28.19 - 16.07 %) From 2018-19 to 2022-23. Similarly, there was a consist upward trend of gross return (96687 – 113545 ha-1), net return (69227 -82273 ha-1) and BC ratio was (3.52-3.63) were found under Integrated Crop Management plots which was higher than Farmer’s Practice. The research study also investigates the changes in area cultivated under improved varieties after the implementation of ICM practices which was increasing 0.13 % from 2018 to 76.34 % in 2022-23.